2011
DOI: 10.1002/ptr.3384
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into the Antiadhesive Activity of Herbal Extracts Against Campylobacter jejuni

Abstract: Campylobacter jejuni is one of the most common bacterial causes of diarrhoea in the industrialized world, being associated with the occurrence of Guillain-Barré Syndrome, and inducing diseases partially through intestinal adherence. With increasing reports of C. jejuni drug resistance against standard antibiotics, investigations into antiadhesive agents for the prevention of bacterial infection are highly significant. Given the consumer-driven development towards holistic and integrative healthcare, research i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 34 publications
1
20
0
1
Order By: Relevance
“…(van Alphen et al, 2012) had similar findings and observed that pre-exposure of C. jejuni to low concentrations of carvacrol modulated motility and invasion of INT-407 intestinal epithelial cells without affecting intracellular ATP levels or epithelial function. Reduced motility and attachment efficiency in C. jejuni on exposure to clove oil (Kovács, 2014), thyme (Pogacar et al, 2016), herbal extracts (Bensch et al, 2011), and campynexins (Johnson et al, 2015) have also been observed.…”
Section: Discussionmentioning
confidence: 99%
“…(van Alphen et al, 2012) had similar findings and observed that pre-exposure of C. jejuni to low concentrations of carvacrol modulated motility and invasion of INT-407 intestinal epithelial cells without affecting intracellular ATP levels or epithelial function. Reduced motility and attachment efficiency in C. jejuni on exposure to clove oil (Kovács, 2014), thyme (Pogacar et al, 2016), herbal extracts (Bensch et al, 2011), and campynexins (Johnson et al, 2015) have also been observed.…”
Section: Discussionmentioning
confidence: 99%
“…This is from the assertion that for many herbal extracts, synergy among multiple constituents exists [51]. The large number of pharmacologically active compounds in the plant increases the likelihood of interactions taking place [52].…”
Section: Discussionmentioning
confidence: 99%
“…Adherence assays were performed using Caco-2 human intestinal cell lines essentially as previously described 54 . Briefly, cells were seeded at 10 5 cells/well in a black wall 96-well cell culture plates in minimal essential medium (MEM) for 48–72 h prior to bacterial challenge.…”
Section: Methodsmentioning
confidence: 99%